Pengaruh Kepuasan Kerja dan Beban Kerja terhadap Kinerja Karyawan Departemen Mutu Checker dry PT. Aneka Bumi Pratama (ABP) Palembang - Muhammad Deni; Arubina Bangsawan; Indah Mawarni; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to determine: (1) The effect of job satisfaction on employee performance of quality checker dry department PT. Aneka Bumi Pratama Palembang. (2)The effect of workload on employee performance of quality checker dry department PT.Aneka Bumi Pratama Palembang.(3) The effect of job satisfaction and workload on employee performance of quality checker dry department PT. Aneka Bumi Pratama Palembang. This is an assosiatif research.The type of datais quantitative dataor inthe formofnumbers.The research instrument uses questionnaires. The populationis employees of PT. Aneka Bumi Pratama Palembang. The sampling technique uses saturated sample.The instrument validity test uses Confirmatory Factor Analysiswhile the reliability test uses Alpha Cronbach. The measuring instrument is validandreliable for research instruments. Multiple regressionanalys is isused to test the hypothesis of this study. The results of the study at 5% significance level found that: (1) job satisfaction has appositive effect on employee performance of quality checker dry department PT. Aneka Bumi Pratama Palembang witht count of 3.281 while t table of 2.028 in addition to the significance value 0 f0.002 also indicates the value is smaller than the alpha value of 0.05. (2) workload has a positive effect on employee performance of quality checker dry department PT. Aneka Bumi Pratama Palembang with t count of 5.947 while the value of t table (n=39,α=5%) of 2.028. Based on these values, t count is greater than t table, inaddition to the significant value smaller than the value of alpha (0.000<0.05). (3) Job satisfaction with F value of 135.064 is greater than F table of 3.26 besides the significance value of 0.000 smaller than the alpha value (n=39,α=5%), PT. Aneka Bumi Pratama Palembang with job satisfaction and workload has a positive and significant effect on employee performance variables.